Estimation of Mean Demand Function for the Poisson Demand Process - Omar, Mohd (Malaysian Journal of Science, 2003)
This paper addresses the problem of determining the best describing parameters in a negative exponentially-declining mean demand and the actual demands follow a Poisson process. Two possible methods will be discussed. The first method is for the periodic review model widely used for the modeling of fast moving items, and the second is for the continuous review model, widely used for the modeling of slow moving items. The methods are illustrated by a numerical example.